2013
DOI: 10.1242/jcs.123232
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal organization of Aurora-B by APC/CCdh1 after mitosis coordinates cell spreading via FHOD1

Abstract: Spatiotemporal regulation of mitotic kinase activity underlies the extensive rearrangement of cellular components required for cell division. One highly dynamic mitotic kinase is Aurora kinase B (AurB), which has multiple roles defined by the changing localization of the chromosome passenger complex (CPC) as cells progress through mitosis, including regulation of cytokinesis and abscission. Like other mitotic kinases, AurB is a target of the anaphase-promoting complex (APC/C) ubiquitin ligase during mitotic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 48 publications
3
39
0
Order By: Relevance
“…AURKB is degraded at the end of mitosis by ubiquitin-mediated degradation in the proteasome [24, 37, 38]. Therefore, it was tested whether depletion of VRK1 might affect the stability of AURKB.…”
Section: Resultsmentioning
confidence: 99%
“…AURKB is degraded at the end of mitosis by ubiquitin-mediated degradation in the proteasome [24, 37, 38]. Therefore, it was tested whether depletion of VRK1 might affect the stability of AURKB.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this model, it was recently shown that the APC/C Cdh1 -mediated degradation of AuroraB controls cell adhesion and spreading occurring »45 min after anaphase onset. 24 Interference with this process causes severe abscission delays. 25 It is, therefore, possible that continuous AuroraB degradation in G1 is critical for abscission onset through the regulation of cell spreading.…”
Section: Resultsmentioning
confidence: 99%
“…U2OS-bio Ub cells and U2OS-BirA cells were obtained via clonal selection with 170 g/ml Hygromycin B (Calbiochem) after transfection of U2OS tet-OFF cells with pTREbio Ub 6 -BirA or pTRE-BirA in a ratio of 10:1 with pCMVhygro and were supplied with 5 M biotin in culture. The hTERT-RPE1 (RPE) cell line stably expressing ␣-actinin-Venus was described previously (33). Cells were synchronized to prometaphase by sequential blocks with 25 mM thymidine and 10 M S-trityl-L-cysteine (STLC, Tocris Bioscience, Bristol, UK) for 20 h and 16 h, respectively, and collected via mitotic shake-off.…”
Section: Methodsmentioning
confidence: 99%
“…We then compared cell spreading in cells expressing wildtype and non-ubiquitinable versions of mCherry-RacGAP1 using hTERT-RPE ␣-actinin-Venus cells in which cell spreading can readily be visualized and quantified (33). Cells electroporated with RacGAP1 constructs were recorded through mitosis by means of fluorescence time-lapse imaging, and the areas of daughter cells, normalized for the area at metaphase, were plotted against time.…”
Section: Fig 5 Apc/c Suppresses Cytoplasmic Racgap1 To Promote Cellmentioning
confidence: 99%